Adenoviral Infections in Singapore: Should New Antiviral Therapies and Vaccines Be Adopted?. (30th September 2019) - Coleman, Kristen K; Wong, Chui Ching; Jayakumar, Jayanthi; Nguyen, Tham T; Wong, Abigail W L; Yadana, Su; Thoon, Koh C; Chan, Kwai Peng; Low, Jenny G; Kalimuddin, Shirin; Dehghan, Shoaleh; Kang, June; et al.
Abstract: Background: A number of serious human adenovirus (HAdV) outbreaks have been recently reported: HAdV-B7 (Israel, Singapore, and USA), HAdV-B7d (USA and China), HAdV-D8, -D54, and -C2 (Japan), HAdV-B14p1 (USA, Europe, and China), and HAdV-B55 (China, Singapore, and France). Methods: To understand the epidemiology of HAdV infections in Singapore, we studied 533 HAdV-positive clinical samples collected from 396 pediatric and 137 adult patients in Singapore from 2012 to 2018. Genome sequencing and phylogenetic analyses were performed to identify HAdV genotypes, clonal clusters, and recombinant or novel HAdVs. Results: The most prevalent genotypes identified were HAdV-B3 (35.6%), HAdV-B7 (15.4%), and HAdV-E4 (15.2%). We detected 4 new HAdV-C strains and detected incursions with HAdV-B7 (odds ratio [OR], 14.6; 95% confidence interval [CI], 4.1–52.0) and HAdV-E4 (OR, 13.6; 95% CI, 3.9–46.7) among pediatric patients over time. In addition, immunocompromised patients (adjusted OR [aOR], 11.4; 95% CI, 3.8–34.8) and patients infected with HAdV-C2 (aOR, 8.5; 95% CI, 1.5–48.0), HAdV-B7 (aOR, 3.7; 95% CI, 1.2–10.9), or HAdV-E4 (aOR, 3.2; 95% CI, 1.1–8.9) were at increased risk for severe disease. Conclusions: Singapore would benefit from more frequent studies of clinical HAdV genotypes to identify patients at risk for severe disease and help guide the use of new antiviral therapies, such as brincidofovir, and potential administration of HAdV 4 and 7 vaccine. Abstract : Human adenovirus (HAdV) outbreaks are often inexplicable with sparse clinical epidemiological data. We sought to describe clinical HAdV genotypes and identify risk factors associated with severe disease among HAdV-positive patients seen at 2 hospitals in Singapore.